2018
DOI: 10.5888/pcd15.170085
|View full text |Cite
|
Sign up to set email alerts
|

Linking Data From Health Surveys and Electronic Health Records: A Demonstration Project in Two Chicago Health Center Clinics

Abstract: IntroductionMonitoring and understanding population health requires conducting health-related surveys and surveillance. The objective of our study was to assess whether data from self-administered surveys could be collected electronically from patients in urban, primary-care, safety-net clinics and subsequently linked and compared with the same patients’ electronic health records (EHRs).MethodsData from self-administered surveys were collected electronically from a convenience sample of 527 patients at 2 Chica… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
5
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 26 publications
1
5
0
Order By: Relevance
“…A previous study reported discrepancies between self‐reported and EHR‐based antibiotic use about 8.3% of the time in adults with CF 20 . Consistent with our findings, non‐CF studies have reported a range of kappa values associated with the two methods for different types of medications: 0.18 for antibiotics, 0.53‐0.64 for chronic medications, and 0.67 for vaccines 21‐23 . A study of pregnant women reported relatively high kappa values for chronic medications (>0.80) and lower kappa values for acute medications (0.35) 24 …”
Section: Discussionsupporting
confidence: 88%
“…A previous study reported discrepancies between self‐reported and EHR‐based antibiotic use about 8.3% of the time in adults with CF 20 . Consistent with our findings, non‐CF studies have reported a range of kappa values associated with the two methods for different types of medications: 0.18 for antibiotics, 0.53‐0.64 for chronic medications, and 0.67 for vaccines 21‐23 . A study of pregnant women reported relatively high kappa values for chronic medications (>0.80) and lower kappa values for acute medications (0.35) 24 …”
Section: Discussionsupporting
confidence: 88%
“…Only in more recent years have institutions begun to start incorporating patient response data related to experience or even social determinants of health. [32] Given the extensive resources dedicated to clinical outcomes, dedicating even a fraction of this attention to the collection and integration of patient experience data would be an impactful first step in our more rigorous understanding the patient experience with respect to hospital readmissions and ways to positively impact patient outcomes. The pairwise comparisons within the factor analysis did demonstrate both some expected and unexpected findings.…”
Section: Discussionmentioning
confidence: 99%
“…Studies that included the prevalence of disease patterns, the prevalence of common diagnostic categories, disease incidence estimates, and measures of concordance between EHR and another data source, all in the context of chronic disease surveillance, were also included [8][9][10][11]. We excluded all studies conducted outside of the U.S.…”
Section: Screening By Relevant Titles/topics and Abstract Contentmentioning
confidence: 99%
“…We excluded all studies conducted outside of the U.S. The number of studies included for qualitative synthesis in the final review was 17 [5,6,[8][9][10][11][12][13][14][15][16][17][18][19][20][21][22][23][24][25].…”
Section: Screening By Relevant Titles/topics and Abstract Contentmentioning
confidence: 99%